Elevated VEGF Levels in Pulmonary Edema Fluid and PBMCs from Patients with Acute Hantavirus Pulmonary Syndrome - Irina Gavrilovskaya; Elena Gorbunova; Frederick Koster; Erich Mackow (Advances in Virology)
Hantavirus pulmonary syndrome is characterized by vascular permeability, hypoxia, and acute pulmonary edema. Vascular endothelial growth factor (VEGF) is induced by hypoxia, potently induces vascular permeability, and is associated with high-altitude-induced pulmonary edema. Hantaviruses alter the normal regulation of β3 integrins that restrict VEGF-directed permeability and hantavirus infected endothelial cells are hyperresponsive to the permeabilizing effects of VEGF. However, the role of VEGF in acute pulmonary edema observed in HPS patients remains unclear. Here we retrospectively evaluate VEGF levels in pulmonary edema fluid (PEF), plasma, sera, and PBMCs from 31 HPS patients. VEGF was elevated in HPS patients PEF compared to controls with the highest levels observed in PEF samples from a fatal HPS case. VEGF levels were highest in PBMC samples during the first five days of hospitalization and diminished during recovery. Significantly increased PEF and PBMC VEGF levels are consistent with acute pulmonary edema observed in HPS patients and HPS disease severity. We observed substantially lower VEGF levels in a severe HPS disease survivor after extracorporeal membrane oxygenation. These findings suggest the importance of patients’ VEGF levels during HPS, support the involvement of VEGF responses in HPS pathogenesis, and suggest targeting VEGF responses as a potential therapeutic approach.